The Five-Category Ontology? : E. J. Lowe and the Ontology of the Divine - Renz, Graham (TheoLogica: An International Journal for Philosophy of Religion and Philosophical Theology, 2021)
E.J. Lowe was a prominent and theistically–inclined philosopher who developed and defended a four–category ontology with roots in Aristotle’s Categories. But Lowe engaged in little philosophical theology and said even less about how a divine being might fit into his considered ontology. This paper explores ways in which the reality of a divine being might be squared with Lowe’s ontology. I motivate the exploration with a puzzle that suggests Lowe must reject either divine aseity or the traditional view that God is a substance. After showing that the puzzle cannot be overcome by rejecting one of its premises, I consider ways in which Lowe might try to reject the puzzle wholesale. I argue that the best way to reject the puzzle is to countenance a fifth fundamental category, the category of supernatural substance.